Optimization of ethanolic extraction of asiaticoside and asiatic acid: A stability study and correlation of dielectric constant - Teerin Chysirichote; Waewwan Wattanasiriwit; Chatchaporn Uraipong (Applied Food Research, 2025)
This study optimized the extraction of asiaticoside and asiatic acid from Centella asiatica using an ultrasonic-assisted extraction method. The research focused on ethanol concentration, extraction temperature, and extraction duration to maximize yield efficiency. In addition, the stability of the extracted compounds was assessed under different temperature and pH conditions for practical applications. The highest asiaticoside yield was achieved using 53.7 % ethanol at 50.0 °C for 35 min., whereas asiatic acid extraction was most efficient using 63.3 % ethanol at 64.3 °C for 28 min. A significant correlation was observed between the dielectric constant of the extraction conditions, which was affected by solvent concentration and temperature, and extraction efficiency. Stability tests showed that temperature had a more pronounced impact than pH, with degradation accelerating at higher temperatures. The findings emphasize the importance of maintaining processing conditions below 70 °C and within an acidic to neutral pH range. These results provide valuable insights for industrial applications in pharmaceutical, cosmetic, and nutraceutical sectors, underscoring the necessity of controlled conditions to preserve the bioactive properties of Centella asiatica extracts.
Keywords: Medicinal Plants and Neuroprotection; Essential Oils and Antimicrobial Activity; Phytochemicals and Medicinal Plants